2022
DOI: 10.3389/fonc.2022.943761
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CNSL at diagnosis of childhood B-cell acute lymphoblastic leukemia: A report from the South China Children’s Leukemia Group

Abstract: ObjectivesThe prognostic significance of acute lymphoblastic leukemia (ALL) patients with central nervous system leukemia (CNSL) at diagnosis is controversial. We aimed to determine the impact of CNSL at diagnosis on the clinical outcomes of childhood B-cell ALL in the South China Children’s Leukemia Group (SCCLG).MethodsA total of 1,872 childhood patients were recruited for the study between October 2016 and July 2021. The diagnosis of CNSL depends on primary cytological examination of cerebrospinal fluid, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Furthermore, central nervous system involvement is associated with inferior survival, and our study also showed poorer outcomes in AML patients with CNS involvement [41][42][43][44].…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, central nervous system involvement is associated with inferior survival, and our study also showed poorer outcomes in AML patients with CNS involvement [41][42][43][44].…”
Section: Discussionsupporting
confidence: 62%